Becoming Manny : inside the life of baseball's most enigmatic slugger - Rhodes, Jean E.; Boburg, Shawn, 1978- (New York : Scribner, 2009)
An authorized biography of baseball player, Manny Ramirez, and his roots, development, and career from the Dominican Republic and Washington Heights to the Hall of Fame.
Keywords: Ramirez, Manny, -- 1972-; Baseball players -- United States -- Biography